The Effect of Cognitive Speed of Processing Training on the Development of Additional IADL Difficulties and the Reduction of Depressive Symptoms: Results From the IHAMS Randomized Controlled Trial. (March 2015) - Wolinsky, Fredric D.; Vander Weg, Mark W.; Howren, M. Bryant; Jones, Michael P.; Dotson, Megan M.
Objective: We evaluated the effects of cognitive speed of processing training (SOPT) on the development of additional Instrumental Activities of Daily Living (IADL) difficulties and the reduction of depressive symptoms in the Iowa Healthy and Active Minds Study (IHAMS).Method: Six hundred eighty-one patients were randomized to 4 groups: 10 hr of on-site SOPT, 10 hr of on-site SOPT plus 4 hr of boosters, 10 hr of at-home SOPT, or 10 hr of on-site attention-control (crossword puzzles). Developing additional difficulties with IADLs and reductions in depressive symptoms 1 year later were evaluated using multiple logistic regression.Results: The on-site SOPT with boosters group had reduced odds of developing additional difficulties with IADLs (adjusted odds ratio [AOR] = 0.45, p = .044) compared with attention-controls. The on-site SOPT with boosters group also had increased odds of reduced depressive symptom levels (AOR = 2.93, p = .003) compared with attention-controls.Discussion: These findings provide evidence that SOPT transfers beyond the cognitive skills trained to meaningful downstream improvements in the lives of middle-aged and older adults.